Analisis Perubahan Tata Guna Lahan Dan Kerentanan Ekosistem DAS Siwa, Sulawesi Selatan - Budi Utomo Putra Azis; Iriansa Iriansa; Agsa Dewantara (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
The Siwa Watershed (DAS Siwa) in South Sulawesi is a strategic ecosystem spanning Wajo, Sidrap, and Luwu Regencies. Uncontrolled land use changes in this area have the potential to reduce ecological carrying capacity and increase ecosystem vulnerability. This study aims to analyze land use changes and ecosystem vulnerability levels in DAS Siwa during the 2015–2025 period using a descriptive quantitative-spatial approach based on Geographic Information Systems (GIS). Data used include multitemporal land use imagery, rainfall data, topographic maps, and administrative boundaries. Analysis shows that the total area of DAS Siwa is 26,866.85 ha, dominated by forest (70.66%) but experiencing deforestation of 552.99 ha (24.37%) during the observation period. Mixed plantations increased significantly by 389.70 ha (17.18%), while settlements and agricultural land also expanded. Ecosystem vulnerability was assessed through a composite index considering land change, rainfall intensity, slope, and vegetation cover. Spatial overlay results identified high vulnerability zones in the central and upstream parts of the watershed, coinciding with active deforestation and high rainfall areas. These findings are expected to serve as a scientific basis for sustainable and ecosystem-based management of DAS Siwa.